Źródła zmienności stóp zwrotu akcji notowanych na GPW - Śmiech, Sławomir (Sources of Volatility of Returns in Warsaw Stock Exchange, 2008)
Multifactor models can be used to explain returns of financial instruments. There are three main groups of multifactor models i.e. fundamental, macroeconomic and statistical factor models. In statistical factor models factors are not directly observable. If one use principal component analysis to extract the factor realizations then it can be interpret as interdependent source of volatility of returns. This article presents results of extracting factors explaining volatility of returns of stocks on the Warsaw Stock Exchange.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 88-95